Examining Key Drivers of International Student Satisfaction in a Chinese University - Wang, Haoli (Scholar: Human Sciences, 2026)
Purpose: The study explores the impact of five independent variables (Access, Academic Services, Administrative Services, Quality of Instructor, and Perceived Usefulness) on the dependent variable (International Student Satisfaction). Additionally, it seeks to determine significant differences between these variables before and after implementing a Strategic Plan (SP). Research design, data, and methodology: The study utilized the Index of Item-Objective Congruence (IOC) for validity and Cronbach’s Alpha for reliability through a pilot test with 30 students. Data was collected from 80 valid responses from international students at a University in China, which were analyzed using multiple linear regression to verify the significant relationships between variables. Following this, a Strategic Plan was implemented, and the quantitative results from post-SP and pre-SP phases were compared using a paired-sample t-test. Results: The multiple linear regression analysis revealed that access, academic services, administrative services, and instructor quality significantly impacted international student satisfaction, while perceived usefulness did not significantly impact it. Additionally, the results from the paired-sample t-test showed a significant difference in international student satisfaction between the post-SP and pre-SP stages. Conclusions: This study aims to enhance international student satisfaction by improving key educational and administrative services at a university and advancing higher education for international students in China.